Software configuration management strategies and IBM Rational ClearCase : a practical introduction - Bellagio, David E. (IBM Press, 2005)
"I wrote that the first edition of this book "communicates much of the experience, wisdom, and insight that was acquired along the way to discovering what SCM best practices are and how to implement/deploy them." The second edition is full of even more practical experience! It not only refines and expands upon earlier strategies and best practices, it also contains even more concrete "how-to" information about implementing and deploying them."--Brad Appleton co-author of Software Configuration Management Patterns: Effective Teamwork, Practical Integration "Read this book when you're getting started with configuration management (CM); read it again in six months and once more two years later. Software Configuration Management Strategies and IBM Rational ClearCase goes beyond the basics to provide a coherent review of CM strategies for projects of all sizes and complexities." -Jennie Brown, CM Specialist IBM Corporation "This book covers practical software configuration management (SCM), ClearCase UCM and ClearCase use for project teams. Every project lead and SCM specialist should (re)read this book before starting a project." -Roger Jarrett, Senior Software Engineer IBM Rational Software "This second edition captures vital Unified Change Management (UCM) features and concepts. It brings the entire UCM feature set full circle and lays the ground work for a successful UCM implementation; Bellagio and Milligan continue where the first edition left off. The inclusion of composite baseline concepts, single stream development, performance tuning, and other features and concepts make this the core of any old or new Unified Change Management implementation. It is rare that a second edition of a book can hold your interest like the first. This publication does just that ... this continues to be the standard for users interested in Unified Change Management deployment." -Adam Levensohn, Manager IBM Rational Software Software Configuration Management (SCM) can help even the largest, most complex project teams manage change, so they can deliver higher quality products faster. The First Edition of Software Configuration Management Strategies and Rational ClearCase established itself as the definitive single source for guidance on both SCM best practices and the market's leading product, IBM Rational ClearCase. This fully updated Second Edition systematically addresses the latest ClearCase and ClearQuest® innovations, while offering even deeper insight into S ...